Problems with Pupils' Reading and Solutions/مشاكل القراءة لدى التلاميذ وحلولها - Jazil Ar-Rahman (JURNAL IJ-ATL, 2018)
Reading is a key factor in building personality and refining it. It provides the reader with the knowledge and experience that he may not be able to acquire directly through reading. It is also the tool of the student in acquiring his academic sciences and expanding knowledge horizons. "Whoever does not read well does not get well," he said. This research deals with the problems of reading among students with all the difficulties surrounding them. These problems arise from the fact that the readable text is boring. Therefore, the reading should use different sources of erotic hearts.القراءة عامل أساسي في بناء الشخصية وصقلها، فهي تزوّد القارئ بالمعارف والخبرات التى قد لا يستطع أن يكتسبها مباشرة إلا من خلال القراءة، كما أنها أداة الطالب في تحصيل علومه الدراسية وتوسيع أفاق المعرفي. فصح من يقول "من لا يقرأ جيدا لا يحصل جيدا". ويتناول هذا البحث عن مشاكل القراءة لدي التلاميذ بكل صعوبات محيطة بها. فإن تلك المشاكل تنبثق من كون النص المقروء جافا مملا. لذا، ينبغي أن تستخدم القراءة مصادر المختلفة المثيرة للقلوب.